THE ROLE OF CHEST CT ANGIOGRAPHY AS A DIAGNOSTIC TOOL AND ROAD MAP FOR THE MANAGEMENT OF RASMUSSEN’S ANEURYSM: A CASE REPORT - Barkah, Maskuril Barkah; Dini R. Erawati; Aslam, Ahmad Bayhaqi Nasir; Setyawan, Agung; Tjakraatmadja, Ricardo (International Journal of Radiology and Imaging, 2022)
Rasmussen’s aneurysm is a pulmonary artery pseudoaneurysm, secondary to the invasion of granular tissues to the pulmonary artery wall, causing massive hemoptysis. A 39-year-old male, with a history of pulmonary TB presented with massive hemoptysis, persistent cough, and dyspnea. Chest X-ray and Chest CT depicted active pulmonary tuberculosis and a co-infection with aspergillosis in the form of aspergilloma. Chest CT angiography (CTA) showed narrow-necked Rasmussen’s aneurysm with the feeding artery coming from the pulmonary artery of the apicoposterior segment and the systemic artery from the left thyrocervical trunk branch and left bronchial artery. Fluoroscopy-guided transarterial embolization with polyvinyl alcohol (PVA) and gel foam was performed from the left bronchial artery and thyrocervical trunk branch followed by transcatheter embolization with glue insertion via the pulmonary artery in the aneurysmal site. After the procedures the embolic agent completely filled the aneurysm and there were no complaints of hemoptysis during the follow-up. Appropriate chest CT angiography procedures can help diagnose Rasmussen’s aneurysm and become a road map for embolization. Transarterial catheter embolization from bronchial or non-bronchial systemic artery and pulmonary artery can be used as the treatment modality of choice for Rasmussen’s aneurysm in pulmonary tuberculosis with aspergillosis co-infection in the form of aspergilloma.